Analysis of growth of sandfish Holothuria scabra cultured at different cultivated habitat - Ambo Tuwo; Joeharnani Tresnati; . Saharuddin (Syiah Kuala University, 2012)
The problem in the sea cucumber culture development in Indonesia is the difficulty to find the culture area that could provide optimal production. This study analyzed the cultivated habitat that could provide optimal growth,proximate and total energy to sandfish Holothuria scabra cultivated in different habitats. The study was done from March to June 2011 in the Puteangin Island, Lasitae Village, District Tanete Rilau, Barru Regency, South Sulawesi.The cage size used was 2 m in length, 1 m in width, and 1.5 m in height. The net mesh-size was 0.5 inch. The cage placed at three different habitats, i.e. sandy overgrown with seagrass habitat, sandy covered with corals habitat, andsandy habitat. The study consisted of three treatments and three replications. Growth was observed by measuring the daily specific growth rate and absolute weight growth. Proximate and energy content of sandfish was analyzed atthe beginning and the end of the study. The study reveals that the sand and seagrass habitat provide the best results with daily specific growth rate is 1.15% ± 0.03%. The absolute weight growth is 28.45 g ± 0.95 g. The proximate content is 0.24 g ± 0.492 g for protein, 0.07 g ± 0.395 g for fat, and 18.026 g ± 0.39 g for carbohydrate. The highest energy content is 176 997 calories.